Model of students’ learning styles at Elementary School - Fahrurrozi, Fahrurrozi; Safitri, Desy; Marini, Arita; Wahyudi, Apri (Opción, 2019)
The aim of this study is to offer a model of students’ learning styles at elemen- tary schools in West Jakarta in Indonesia. This model suggests that students’ learning styles can be predicted by visual, auditory, and kinesthetic learning style. Data were collected from 276 students at grade three from elementary schools in West Jakarta in Jakarta Province in Indonesia. Structural Equa- tion Modeling (SEM) was used to analyse the data in this study. The result of this study found that visual, auditory, and kinesthetic learning styles estimate students’ learning styles. Other finding also confirmed that students prefer- ring remember what they see to what they hear, students interested in symbol, picture, and colors, and students interested in reading predict student visual learning style. Another finding suggested that students learning by listening, students reading loudly, and students judging people by the sound of their voices influence auditory learning style. Students expressing emotion physi- cally, students enjoying using body language, and students remembering well what they have done encourage kinesthetic learning style.